Smartphone Addiction and Eysenck's Personality Traits Among Chinese Adolescents: A Meta-Analysis - Xiong, Sicheng; Xu, Yi; Zhang, Bin; Zhu, Lihui; Xie, Jianhui (Frontiers in Psychology, 2022)
With the quickly rising popularity of smartphone among adolescents over the past decade, studies have begun to investigate the relationship between smartphone addiction and Eysenck’s personality traits. Despite numerous studies on this topic, however, findings have been mixed and there is a lack of consensus regarding this relationship. Thus, this meta-analysis aimed to explore the relationship between smartphone addiction and Eysenck’s personality traits in Chinese adolescents, as well as its possible moderators. Through literature search and screening, 33 studies were included, comprising 79 independent effect sizes with a total of 17, 737 subjects. A random effects model was selected, and it was found that smartphone addiction was positively associated with psychoticism (r = .16, p < .001) and neuroticism (r = .32, p < .001), but not significantly associated with extroversion (r = -.06, p = .079). The moderating effect test showed that gender had a significant influence on the relationships between smartphone addiction and both psychoticism and neuroticism, while the year of study publication had a significant influence on only the relationship between smartphone addiction and psychoticism. This study is the first meta-analysis on the relationship between smartphone addiction and Eysenck’s personality traits among adolescents in China, and the results have helped to clarify the controversy of previous studies regarding this relationship.